AGRARIAN ISSUE: PEASANT AND AGRICULTURE DEVELOPMENT IN CAPITALISM - Oliveira Valerio, Valmir Jose de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2021)
In agriculture, the development of capitalism causes the peasantry to have its existence constantly threatened, since capitalist relations weigh on these problems and conflicts arising from a permanently updated process between capital and labor, which can be analyzed through the concept of an agrarian issue. In this sense, this article seeks to analyze some of the main theoretical and conceptual elements of this process, especially regarding the contradictory nature of the development of capitalism in the countryside. For that, some of the reference works for the debate were used, with emphasis on the contributions of Kautsky (1980), Lenin (1985), Luxemburg (1985) and Chayanov (1981). Together, these works offer subsidies for the analysis and understanding of problems that, until today, keep the agrarian question as an essential process for understanding the evolution of capitalism in the countryside.
Keywords: Agrarian issue; Peasantry; Capitalist agriculture